STUDY ON ALGAL GROWTH IN ISAHAYA RESERVOIR - P. Ittisukananth; K. Koga; N. Vongthanasunthorn (International Association of Lowland Technology, 2008)
Isahaya reservoir was constructed at the innermost sea of Isahaya Bay, Japan, in 1997 for preventing natural disasters and developing water resources. Algal growth in this reservoir has been changed since the beginning of the Isahaya-Bay Sea Reclamation Project. As the result, the main purpose of this study is to investigate the effect of algae growth in the Isahaya reservoir using a water quality model. In mass balance equation of this model, several interactions among water quality parameters, namely chlorophyll-a (Chl-a), chemical oxygen demand (COD), suspended solid (SS), total nitrogen (TN), dissolved inorganic nitrogen (DIN), total phosphorus (TP), dissolved inorganic phosphorus (DIP) and chloride (Cl-), are incorporated. Sensitivity analysis reveals that nutrients in the Isahaya reservoir are contributed from land area, resuspension-release from mud bed, and coagulation-flocculation-precipitation by seawater. This study found that, before fiscal year 2000, lime (calcium hydroxide, Ca(OH)2) which is used for soil improvement was one of algal growth inhibition in the Isahaya reservoir. Since fiscal year 2000, diatom is the most dominant algal species in this reservoir.